From Central Asia to South Africa: In Search of Inspiration in Rock Art Studies - Rozwadowski, Andrzej (Werkwinkel, 2017)
The paper describes the story of discovering South African rock art as an inspiration for research in completely different part of the globe, namely in Central Asia and Siberia. It refers to those aspect of African research which proved to importantly develop the understanding of rock art in Asia. Several aspects are addressed. First, it points to importance of rethinking of relationship between art, myth and ethnography, which in South Africa additionally resulted in reconsidering the ontology of rock images and the very idea of reading of rock art. From the latter viewpoint particularly inspiring appeared the idea of three-dimensionality of rock art ‘text’. The second issue of South African ‘origin,’ which notably inspired research all over the world, concerns a new theorizing of shamanism. The paper then discusses how and to what extent this new theory add to the research on the rock art in Siberia and Central Asia.